United States - Ecuador Relations. In the shade of September 11 - Espinosa, Carlos (2016)
This article explores how the relations between Ecuador and the United States could change as a consequence of the current war against terrorism. It addresses also what role could Ecuador perform in the US trade and oil-related strategies. Its main conclusion is that the temptation of becoming closely aligned with the US foreign policy will be difficult to avoid.